An Analysis of Presupposition in The Selected Song Lyrics in The Sour Album by Olivia Rodrigo - Christhy Febbriantika Cisilia Beth; Gurendi Wiwoho (Universitas 17 Agustus 1945 Semarang, 2022)
Text is a language that contains sentences that express someone’s feelings, thoughts, and messages. Song lyrics as a form of text certainly contains meanings or messages addressed by the speaker to readers. In this study, the writer is interested in analyzing to discuss the types of presupposition, the predominant ones, and the implied meaning in selected song lyrics in the Sour album. The research method used is descriptive qualitative. In this study the writer choose five song lyric in the Sour album such as “Driver License”, “Good 4 U”, “Déjà vu”, “Happier”, and “Traitor”. The result of this study can be summarize as follows. Firstly, there are various kinds of presupposition are found such as existential, factive, lexical, non-factive, structural, and counterfactual. Secondly, the predominant types presupposition is factive, with the assumes that the song lyrics is fact based on subjectify of the speaker. Finally, the meanings implied in the song lyrics of this study mostly indicate expressions of love and broken heart.Keywords: pragmatics, presupposition types, presupposition meaning, predominant presupposition, song lyrics.